Experience of Approbation of Scientific-Research Module in Magistracy Profile "Teacher of Elementary General Education" - Zakharova I.M. (Психолого-педагогические исследования)
The article presents the experience of testing of the module of master's basic professional educational program in the direction of training "Teacher of primary general education" under network interaction between university and school (professional master’s course). The necessity of content and form changing of future primary school teachers’ training in the aspect of practical orientation strengthening is defined. The need for network interaction between university and school is determined by new requirements to the level of master’s professional competencies’ development. Changes in the content, forms and methods of work with students in the aspect of the activity-competence approach implementation to their training are normatively substantiated. The routes of cooperation between a supervisor and a teacher to assess the level of labor actions’ development of undergraduates are settled. The results of the module testing are described; the main difficulties of undergraduates in application of activity-based technologies at practical tasks fulfillment are determined. Recommendations on the results of the module testing are presented